Assessing the educational needs of urban gardeners and farmers on the subject of soil contamination - Harms, Ashley Marie Raes; Presley, DeAnn R.; Hettiarachchi, Ganga M.; Thien, Stephen J. (My University, 2013)
Participation in urban agriculture is growing throughout the United States; however, potential soil contaminants in urban environments present challenges. Individuals in direct contact with urban soil should be aware of urban soil quality and soil contamination issues to minimize environmental and human health risks. The study reported here assessed the needs of urban gardeners and farmers throughout the United States with respect to soil contamination. Our results suggest that urban gardeners and farmers need and want information and guidance on best management practices for safely growing food crops on mildly contaminated urban soils.
Citation: Harms, A. Presley, D., Hettiarachchi, G. M., & Thien, S. J. (2013). Assessing the Educational Needs of Urban Gardeners and Farmers on the Subject of Soil Contamination. Journal of Extension, 51(1). https://www.joe.org/joe/2013february/a10.php
Keywords: Urban agriculture; Soil contaminants; Urban gardeners; Urban farmers